Hôtel-Dieu in Paris: material, structural and functional reforms, between twelve and eighteenth centuries - Cristina Teresa Morales (Universidad de Alicante, 2013)
The objective of the present study is discover and disclose the history of the Hôtel-Dieu in Paris between twelve and eighteenth centuries, period of time when some big facilities where built the administration system was changed and an Agustinian Sisters functional structure was developed with the implementation of supervisors and some specialist in different areas. The methodology used in this study is cualitative-descriptive that begins with the bibliography research and followed by an hermeneutic analysis of the documents that were found. The conclusions of this revision relate to the issue of the difficulties faced in order to change from and caritative-religious management of the sanitary assistance to a laic management, loosing in this process it altruistic conception; the development of this high-scale facility for sanitary attention and also the administration, both hierarchy and functional. All this during a wide six centuries.